RETRACTED: Screen Time and Body Mass Index Among Children and Adolescents: A Systematic Review and Meta-Analysis - Wu, Yiling; Amirfakhraei, Azita; Ebrahimzadeh, Farnoosh; Jahangiry, Leila; Abbasalizad-Farhangi, Mahdieh (Frontiers in Pediatrics, 2022)
Background: There is no summative quantitative study that report the difference in BMI in high screen user children and adolescents or give a difference in screen time in obese versus non-obese children and adolescents. In the current meta-analysis we systematically summarized the association between obesity and screen time and meta-analyzed the results. Methods: A systematic search from Scopus, PubMed and Embase electronic databases. Studies that evaluated the association between screen time and obesity up to June 2021. Results: Results revealed that those at the highest screen time category had 0.7 kg/m2 higher BMI (WMD= 0.703; CI= 0.128, 1.278; P < 0.016; I2 = 95.8%). Moreover, obese children and adolescents had a mean value of 0.313 hours higher screen time compared with non-obese children and adolescents (WMD: 0.313; OR= 0.219, 0.407; P <0.001; I2= 96%). The results of subgrouping showed that study quality, continent and sample size could reduce the heterogeneity values. No evidence of publication bias was reported according to visual asymmetry of funnel plots and the results of Begg’s and Egger’s tests. Conclusion: For the first time, the current systematic review and meta-analysis revealed a positive association between screen time and obesity among children and adolescents. Due to the cross-sectional deign of the included studies, causal inference is impossible, therefore, further studies in separate analysis of both genders are suggested to better elucidate gender-specific results. Registration: The work has also been registered in PROSPERO (Registration number: CRD42021233899).